Interplay between RNA-binding protein HuR and Nox4 as a novel therapeutic target in diabetic kidney disease - Qian Shi; Doug-Yoon Lee; Denis Féliers; Hanna E. Abboud; Manzoor A. Bhat; Yves Gorin (Elsevier, 2020)
Objective: Glomerular injury is a prominent pathological feature of diabetic kidney disease (DKD). Constitutively active NADPH oxidase 4 (Nox4) is a major source of reactive oxygen species that mediates hyperglycemia-induced mesangial cell (MC) fibrotic injury. However, the mechanism that Nox4 utilizes to achieve its biological outcome remains elusive, and the signaling pathways that regulate this isoform oxidase are not well understood. Here, our goal is to study the detailed mechanism by which NAPDH oxidase 4 (Nox4) is post-transcriptionally regulated in MC during diabetic pathology. Methods: We studied the protein expression of HuR, Nox4 and matrix proteins by western blotting, while we assessed the mRNA stability of Nox4 by RT-PCR and polysomal assay, examined in vitro cultured glomerular mesangial cells treated by high glucose (HG) and diabetic animal induced by STZ. The binding assay between HuR and the Nox4 promoter was done by immuno-precipiating with HuR antibody and detecting the presence of Nox4 mRNA, or by pull-down by using biotinlyated labeled Nox4 promoter RNA and detecting the presence of the HuR protein. The binding was also confirmed in MCs where Nox4 promoter-containing luciferage constructs were transfected. ROS levels were measured with DHE/DCF dyes in cells, or lucigenin chemiluminescence for Nox enzymatic levels, or HPLC assay for superoxide. HuR protein was inhibited by antisense oligo that utilized osmotic pumps for continuous delivery in animal models. The H1bAc1 ratio was measured by an ELISA kit for mice. Results: We demonstrate that in MCs, high glucose (HG) elicits a rapid upregulation of Nox4 protein via translational mechanisms. Nox4 mRNA 3' untranslated region (3'-UTR) contains numerous AU-rich elements (AREs) that are potential binding sites for the RNA-binding protein human antigen R (HuR). We show that HG promotes HuR activation/expression and that HuR is required for HG-induced Nox4 protein expression/mRNA translation, ROS generation, and subsequent MC fibrotic injury. Through a series of in vitro RNA-binding assays, we demonstrate that HuR acts via binding to AREs in Nox4 3'-UTR in response to HG. The in vivo relevance of these observations is confirmed by the findings that increased Nox4 is accompanied by the binding of HuR to Nox4 mRNA in kidneys from type 1 diabetic animals, and further suppressing HuR expression showed a reno-protective role in a type 1 diabetic mouse model via reducing MC injury, along with the improvement of hyperglycemia and renal function. Conclusions: We established for the first time that HuR-mediated translational regulation of Nox4 contributes to the pathogenesis of fibrosis of the glomerular microvascular bed. Thus therapeutic interventions affecting the interplay between Nox4 and HuR could be exploited as valuable tools in designing treatments for DKD.